ANALISIS PENGARUH INDIKATOR MEKANISME COORPORATE GOVERNANCE PENGUATAN INTEGRITAS 360 DERAJAT TERHADAP KINERJA PEGAWAI PADA KANTOR PENGAWASAN DAN PALAYANAN BEA CUKAI TIPE MADYA PABEAN TANJUNG PERAK - Alief Umangi Jawantha; Sri Rahayu; Rifda Fitrianty (MANAJEMEN DEWANTARA, 2026)
Purpose: This study aims to examine the effect of 360-degree integrity strengthening as a Corporate governance mechanism on employee performance at the Customs and Excise Supervision and Service Office Type Madya Pabean Tanjung Perak. Research Method: This study used a quantitative causal-associative approach. The population consisted of 377 active civil servants, and 79 respondents were selected using the Slovin formula with a 10% error rate. Data were collected through a five-point Likert-scale questionnaire and analyzed using simple linear regression with SPSS 23. Result: The instruments were valid and reliable. The regression results indicate that 360-degree integrity strengthening has a positive and significant effect on employee performance (B = 0.849; beta = 0.410; t = 3.941; p < 0.05). The coefficient of determination shows that the model explains 16.8% of the variance in employee performance. These findings imply that integrity strengthening contributes to performance improvement, although other organizational and individual factors remain relevant